Reaktualisaasi Konsep Kafa’ah Dalam Bingkai Perubahan Sosial Di Kabupaten Lamongan - Muh. Makhrus Ali Ridho; Ja’far Shodiq (HUMANISTIKA : Jurnal Keislaman, 2021)
This research aims to show the change of kafa’ah concept on the social transformation in Lamongan District. Kafa’ah is equality between husband and wife in a family on certain compont. kafa’ah is preventife strategy to minimize difference between husband and wife. This difference can to be a conflict in a family. On islamic law (Hanafi school), componts of Kafa’ah are; cognation, Islam, independence, Propert and piety. But, the social change motivate to reactualisation of kafa’ah concept. The this componts in Lamongan District are; cognation, education, piety, profession and salary.